1989
DOI: 10.1002/actp.1989.010400305
|View full text |Cite
|
Sign up to set email alerts
|

Fällungsstrukturen aus Polymerlösungen für Trennmaterialien

Abstract: Für die Herstellung von Trennmaterialien nach dem Phaseninversionsverfahren ist der Übergang des Polymers aus der Lösung über die Gelphase in eine Fällungsstruktur charakteristisch. Nach Erörterung von Grundlagen der Fällungsstrukturbildung sowie der Darstellung experimenteller Ergebnisse mit Hilfe der Lichtstreuung werden die Formierung von Flachmembranen aus Cellulose‐2,5‐acetat, die Herstellung von Cellulosehohlmembranen nach dem Viskoseverfahren sowie die Bildung von Mikrokapseln aus Polyanion‐Polykation‐K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the present work, we discuss a different procedure to produce polyHIPE from premade homopolymers and block copolymers, whose emulsification based on selective solvent casting does not require any polymerization process. Although a wide range of morphologies can be obtained by solvent casting, we will show that only a specific selection of solvents, copolymers, and homopolymer molecular weights leads to the production of polyHIPE blends. In particular, it will be demonstrated that a suitable emulsion process leads to metastable polyHIPE morphologies in which the high internal phase volume ratio is well beyond that of close packing of spherical domains of the discrete phase.…”
Section: Introductionmentioning
confidence: 87%
“…In the present work, we discuss a different procedure to produce polyHIPE from premade homopolymers and block copolymers, whose emulsification based on selective solvent casting does not require any polymerization process. Although a wide range of morphologies can be obtained by solvent casting, we will show that only a specific selection of solvents, copolymers, and homopolymer molecular weights leads to the production of polyHIPE blends. In particular, it will be demonstrated that a suitable emulsion process leads to metastable polyHIPE morphologies in which the high internal phase volume ratio is well beyond that of close packing of spherical domains of the discrete phase.…”
Section: Introductionmentioning
confidence: 87%